2020
DOI: 10.21439/conexoes.v14i1.1830
|View full text |Cite
|
Sign up to set email alerts
|

Adequação De Serviços De Alimentação Às Boas Práticas De Fabricação

Abstract: A segurança na produção de alimentos pode ser obtida por meio da adoção de práticas adequadas de manipulação, uma vez que estas os protegem de contaminações físicas, químicas e biológicas. Por isso, a Agência Nacional de Vigilância Sanitária (ANVISA) exige, por meio de leis, o cumprimento de boas práticas de fabricação (BPF) de alimentos. Com o presente estudo, portanto, objetivou-se verificar o grau de adoção das ações para controle higiênico-sanitário dos alimentos produzidos em serviços de alimentação e a a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
0
6
0
7
Order By: Relevance
“…Therefore, these programs aim to improve the hygiene and health conditions, covering all food processing, which leads to a positive fact regarding the protection of public health, applying checklists in the food producing entities, so that it is possible to obtain a diagnosis of the situation and propose adjustments and/or improvements through GMP (De OLIVEIRA et al, 2020).…”
Section: Página | 3314mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these programs aim to improve the hygiene and health conditions, covering all food processing, which leads to a positive fact regarding the protection of public health, applying checklists in the food producing entities, so that it is possible to obtain a diagnosis of the situation and propose adjustments and/or improvements through GMP (De OLIVEIRA et al, 2020).…”
Section: Página | 3314mentioning
confidence: 99%
“…For Silva et al, (2008), who through the Popular Restaurants program evaluated the Food Security policy and the hygienic-sanitary quality in the State of Rio Grande do Norte, he concluded that these establishments did not offer sanitary quality food. De Oliveira et al, (2020), when verifying the index of the presence of actions for sanitary hygienic control of the produced food and the legal accordance of the R. bras. Tecnol.…”
Section: Página | 3318mentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a manifestação de uma DTA pode ocorrer na forma de infecção, intoxicação e/ou toxinfecção, apresentando como sintomas mais comuns diarreias, vômitos, náuseas e dores abdominais (MENDONÇA et al, 2020;MELO, 2015).…”
Section: Introductionunclassified
“…É necessário a avaliação das Boas Práticas de Fabricação nas entidades que produzem alimentos, tensionando assim a melhoria das condições de higiene e saúde que abrangem a fabricação dos produtos, de modo que se obtenha um diagnóstico da situação, propondo ajustes e/ou aperfeiçoamento (DE OLIVEIRA et al, 2020).…”
Section: Introductionunclassified